Helmets, head injury and concussion in sport - Bonfield, C. M.; Shin, S. S.; Kanter, A. S. (The Physician and Sportsmedicine, 2015)
Research on the mechanism of concussion in recent years has been focused on the mechanism of injury as well as strategies to minimize or reverse injury. Sports-related head injury research has led to the development of head protective gear that has evolved over the years. Headgears have been designed to protect athletes from skull fractures, subdural hemorrhages and concussions. Over the years, through experience of athletes and continued scientific research, improvements in helmet design have been made. Although these advances have decreased the number of catastrophic injuries throughout sports, the effects on concussions are promising, but largely unproven. In this review, we will discuss development of helmets and studies analyzing their level of protection for both concussion and head injury. This will help us understand what future developments are still needed to minimize the risk of concussion among athletes in various forms of sports.